Carbenes made easy: formation of unsymmetrically substituted N-heterocyclic carbene complexes of palladium(II), platinum(II) and gold(I) from coordinated isonitriles and their catalytic activity - Hashmi, A. Stephen K.; Lothschütz, Christian; Böhling, Constantin; Hengst, Tobias; Hubbert, Christoph; Rominger, Frank (Advanced synthesis & catalysis, 2010)
From palladium(II) or platinum(II) bis(isonitrile) complexes and from gold(I) isonitrile complexes, both easily available from simple precursors, the corresponding mono-N-heterocyclic carbene (NHC) complexes could be obtained selectively in good yields under very mild conditions. The reagents are simple β-chloroammonium salts in the presence of a weak base. Unsymmetric NHC complexes are accessible. Thus over only two steps from simple metal precursors a broad variety of NHC complexes is available, the method is ideal to quickly assemble catalyst libraries. The palladium complexes are active pre-catalysts in Suzuki cross-coupling even with the additional isonitrile ligand on palladium.
First published: 16 November 2010
Gesehen am 27.03.2023